The Politics of Selection: The Historic Sites and Monuments Board of Canada and the Imperial Commemoration of Canadian History, 1919-1950 - Pelletier, Yves (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2006)
AbstractThis article is a preliminary inquiry into the selection process used by the Historic Sites and Monuments Board of Canada (HSMBC) in making its recommendations for the national historic significance of sites, events and individuals between 1919 and 1950. It argues that, while the HSMBC was composed of dedicated and leading figures in the field of Canadian history, Board members operated for its first 30 years almost exclusively as a Victorian gentlemen’s club, without a system of checks and balances. The ideological dominance of the British imperial mindset influenced Board members’ field of historical interests as well as their recommendation for national historic designations of sites, events or individuals. These points will be illustrated by examining the origins and the operations of the HSMBC between 1919 and 1950, and the recommendations for national historic designation presented to the HSMBC by two prominent Board members: Brigadier General Ernest Cruikshank and Dr. John Clarence Webster.